Non-numeric key processing for file indexing using hashing approach - Selamat, Harihodin (Penerbit UTM Press, 1990)
This paper describes the processing tehcnique of non-numeric record key for the purpose of storage and retrieval. Hashing approach is employed in the design and experiments to facilitate the addressing machanism. Link-list approach is adopted to handle synonyms. Basic file organisations are discussed very briefly in order to establish a common basis of terminology and concepts.